Efektifitas Lumatan Daun Jambu Biji (Psidium guajava linn) Terhadap Penyembuhan Luka Bakar (Vulnus combustion) Pada Kelinci - Wahyudi, Wahyudi Wahyudi; Perbina, Dian Ika (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2019)
Guava (Guava guajava linn) or guava contains high pectin so it can lower cholesterol, contain tannins that serves to improve the digestive system. Chemical compounds contained in the fruit guava echoes its shape is quersetin i.e. the type of flavonoid compounds a flavonol, flavones, and flavol, which helps them were to treat the fragility of capillaries in the human. The purpose of this research is to know the effectiveness of guava leaf lumatan (Guava guajava linn) in burn healing in rabbits. The methods used in this study was an experimental method using a control group, the Group and the comparison group test (perlakuaan). The results showed that of the negative control group provides the longest healing impact i.e. on the 13th, the positive control healing burns on day 8, and control using lumatan guava leaf healing burns on day 9 control group comparison, bioplacenton indicates days of healing Burns most rapidly healed.